Pure tone audiometric findings in HIV positive adults in university of Port Harcourt teaching hospital - Uju, Ibekwe Matilda; Dennis, Alasia Datonye (International Journal of Research in Medical Sciences, 2021)
Background: It is known that HIV infection is a risk factor for hearing loss. Therefore this study is to determine the pattern and severity of hearing loss and whether there is a correlation between the CD4 count and hearing impairment in the HIV positive adult patients seen in the infectious outpatient clinic of university of Port Harcourt teaching hospital (UPTH). Methods: A hospital based descriptive cross sectional study of consecutive patients that are HIV positive seen in the infectious outpatient clinic of UPTH within a period of three months, from May to July of 2020. The biodata, history of hearing difficulties and management of the disease was obtained using a semi structured questionnaire. All the patients had otoscopy done and hearing assessment with pure tone audiometry (PTA). The analysis was done with the SPSS version 25 software at a 95% confidence interval and a p value less than 0.05 was considered significant. Results: The study involved 234 subjects comprising 127 males and 107 females. Hearing impairment was seen in n=113 (48.29%). The patients with CD4 count less than 500 cells/mm2 was found to have more hearing loss; 55.8% than those with counts greater than 500 cells/mm2. Age distribution was statistically significant with a p=0.0001. Conclusions: The pure tone audiometric pattern in the majority of the studied population was more of CHL. The age, duration of ARVT and the CD4 count all had statistically significant association with hearing loss in the HIV positive adults.